2006
DOI: 10.1159/000093058
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship between Speech- and Nonspeech-Evoked Auditory Brainstem Responses

Abstract: Auditory brainstem response (ABR) reflects activation of the neural generators along the ascending auditory pathway when a sound is heard. In this study, we explored the relationship between brainstem encoding of click and speech signals in normal-learning children and in those with language-based learning problems. To that end, ABR was recorded from both types of stimuli. We found that the normal pattern of correlation between click- and speech-evoked ABRs was disrupted when speech-evoked ABRs were delayed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
99
0
17

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(129 citation statements)
references
References 72 publications
13
99
0
17
Order By: Relevance
“…To our knowledge, this is the first study to show a developmental time course beyond 2 years for encoding stimulus properties in the human brainstem. Furthermore, although studies have addressed how the brainstem FFR responds to speech (Galbraith et al, 1995(Galbraith et al, , 1997Krishnan, 1999Krishnan, , 2002Krishnan, , 2005Russo et al, 2004;Johnson et al, 2005), the development of the FFR to speech, which is thought to operate via different mechanisms/pathways than the onset response (Hoormann et al, 1992;Kraus and Nicol, 2005;Song et al, 2006;Akhoun et al, 2008), is unknown. Our data show that latency delays in the young group do not become greater at transient peaks later in the response, consistent with the possibility that latency delays in the FFR are being inherited from wave V. The extent to which developmental differences in the frequency domain reflect mechanisms that are independent from those observed in the time domain remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first study to show a developmental time course beyond 2 years for encoding stimulus properties in the human brainstem. Furthermore, although studies have addressed how the brainstem FFR responds to speech (Galbraith et al, 1995(Galbraith et al, , 1997Krishnan, 1999Krishnan, , 2002Krishnan, , 2005Russo et al, 2004;Johnson et al, 2005), the development of the FFR to speech, which is thought to operate via different mechanisms/pathways than the onset response (Hoormann et al, 1992;Kraus and Nicol, 2005;Song et al, 2006;Akhoun et al, 2008), is unknown. Our data show that latency delays in the young group do not become greater at transient peaks later in the response, consistent with the possibility that latency delays in the FFR are being inherited from wave V. The extent to which developmental differences in the frequency domain reflect mechanisms that are independent from those observed in the time domain remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that click and speech stimuli impose different encoding demands on the brainstem. Specifically, a subset of children with learning and literacy disorders show abnormal neural encoding of speech in the presence of a normal clickevoked brainstem response (Cunningham et al, 2001;King et al, 2002;Wible et al, 2004Wible et al, , 2005Banai et al, 2005;Johnson et al, 2005Johnson et al, , 2007Russo et al, 2005;Song et al, 2006). Of particular interest are the peak latency differences that occur within the first 10 ms of the response, the portion of the neural response thought to be most congruent across stimuli and generated within the IC.…”
Section: Introductionmentioning
confidence: 99%
“…The BAEP is generated by synchronous firing of neurons in structures along the ascending auditory pathway including the auditory nerve, cochlear nuclei, superior olivary nucleus, lateral lemniscus and inferior colliculus (5,6,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that women on average have higher ABR peak amplitudes and shorter peak latencies in comparison to men (Burkard et al, 2006). A different study on transient responses concluded that to evaluate hearing loss in infants the best way is to monitor wave V of the ABR to click stimuli (Picton and Durieux-Smith, 1978); however, a later study on children with learning problems and normal-learning abilities showed that while click evoked ABRs can be used to evaluate integrity of cochlea and the ascending auditory pathway, to gather information on the encoding process in the auditory system, speech-evoked ABRs need to be used (Song et al, 2006).…”
Section: Related Workmentioning
confidence: 99%
“…The second difference is in the stimuli used in this study. In the majority of the previous works, the stimuli used were either consonant-vowel syllables (Cunningham et al, 2001;Wible et al, 2005;Russo et al, 2004;Song et al, 2006;Wible et al, 2004) or tones and clicks (Schrode et al, 2014;Starr et al, 1996;Sininger, 1993), but in this study we used pure vowels as stimuli. The main reason for choosing vowels as stimuli in this study was that different vowels have distinct spectral features; and since our goal was to use automatic speech recognition methods for discriminating between speechevoked ABRs, the vowels were chosen over other stimuli for an initial investigation of the proposed approach.…”
Section: Related Workmentioning
confidence: 99%